Proceedings of the 5th International Conference on Physical Education, Sport, and Health (ACPES 2019) 2019
DOI: 10.2991/acpes-19.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Parenting Style and Physical Activity Participation among Adolescents

Abstract: Parents play an important role in the development of healthy lifestyle behaviors in their children. Therefore, this study was conducted to determine the relationship between parenting style and physical activity participation. A random 100 student's aged range from 13 to 17 years old were selected as respondents of this study. The Physical Activity Questionnaire for Adolescences (PAQ-A) was used as the instrument to measure respondent's general level of physical activity meanwhile the Parenting Style Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…Meanwhile, adolescents with parents with high education levels will have a high physical activity level of. 20 The findings of this study are also supported by a previous study, which also found a significant relationship between parental education level and physical activity among adolescents, 21,22 especially in adolescents with obesity. 23 Falese et al (2021) explained that high physical activity levels among adolescents who have parents with high education levels because parents with high education are more likely to support youth involvement in physical activity, like choosing schools that can promote physical activity for their adolescents.…”
Section: Discussionsupporting
confidence: 88%
“…Meanwhile, adolescents with parents with high education levels will have a high physical activity level of. 20 The findings of this study are also supported by a previous study, which also found a significant relationship between parental education level and physical activity among adolescents, 21,22 especially in adolescents with obesity. 23 Falese et al (2021) explained that high physical activity levels among adolescents who have parents with high education levels because parents with high education are more likely to support youth involvement in physical activity, like choosing schools that can promote physical activity for their adolescents.…”
Section: Discussionsupporting
confidence: 88%